2021
DOI: 10.1002/1348-9585.12260
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged sedentary time under the state of emergency during the first wave of coronavirus disease 2019: Assessing the impact of work environment in Japan

Abstract: Objectives The coronavirus disease 2019 (COVID‐19) outbreak and the resulting state of emergency have restricted work environments, which may contribute to increased duration of sedentary behaviors. This study investigated the self‐reported sedentary time of Japanese workers during and after the first state of emergency (April 7 to May 25, 2020) and examined differences in sedentary time after starting work from home and according to job type. Methods We used cross‐sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
12
0
3
Order By: Relevance
“…This is especially challenging in modern society where our attention is constantly pulled into different directions. Multitasking, 6 increased sedentary time, 7 and, more recently, zoom fatigue 8 are health-related issues that have increased among remote workers in recent years. The demands of doing remote work without a set structure and our desire to live a flexible lifestyle require a new, individual approach to sustainable productivity.…”
Section: Well-being On a Day-to-day Basismentioning
confidence: 99%
“…This is especially challenging in modern society where our attention is constantly pulled into different directions. Multitasking, 6 increased sedentary time, 7 and, more recently, zoom fatigue 8 are health-related issues that have increased among remote workers in recent years. The demands of doing remote work without a set structure and our desire to live a flexible lifestyle require a new, individual approach to sustainable productivity.…”
Section: Well-being On a Day-to-day Basismentioning
confidence: 99%
“…To correct for the selectivity of internet-based samples, we used a population-based sample from the CSLC that was representative of the Japanese population. The full details of the methods used can be found in a previous study that used JACSIS data 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding home workers' lifestyle, being confined to the house may have resulted in less physically activity and more sedentary behavior during the COVID-19 pandemic (5)(6)(7)(8)(9)(10). Earlier studies during the first year of the pandemic have observed an association of working from home with reduced physical activity and increased sedentary behavior (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding home workers' lifestyle, being confined to the house may have resulted in less physically activity and more sedentary behavior during the COVID-19 pandemic (5)(6)(7)(8)(9)(10). Earlier studies during the first year of the pandemic have observed an association of working from home with reduced physical activity and increased sedentary behavior (5)(6)(7)(8)(9)(10). In addition, in our recent longitudinal study among 33,325 Dutch workers, we found home workers during the first year of the COVID-19 pandemic to be less likely to be physically active and more likely to be sedentary than location workers (11).…”
Section: Introductionmentioning
confidence: 99%